Bidirectional Coupling Scheme of Chaotic Systems and its Application in Secure Communication System - Mustafa, Mamat; Aceng, Sambas; WS, Mada Sanjaya (2015)
In this paper, in order to show some interesting phenomena of three dimensional autonomous ordinary differential equations, the chaotic behavior as a function of a variable control parameter, has been studied. The initial study in this paper is to analyze the phase portraits, the Lyapunov exponents, the Poincaré maps and the bifurcation diagrams. Moreover, some appropriate comparisons are made to contrast some of the existing results. Finally, the effectiveness of the bidirectional coupling scheme between two identical Jerk circuits in a secure communication system is presented in details. Finally, the simulation results are shown to demonstrate that the proposed method is correct and feasible.